2014
DOI: 10.2466/16.15.pr0.115c16z5
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Sexual Offending Behavior in People with Autism Spectrum Disorder who have Undergone a Psychiatric Forensic Examination

Abstract: The increased awareness of Autism Spectrum Disorders (ASD) over the last few decades as well as the potential association between ASD and offending behaviors has spurred a need for increased research in this area. In order to explore any possible relationship between ASD and violent or sexual crime the present study examines all forensic examination reports over a 10-yr. period in Norway where the charged persons were diagnosed with ASD and charged with either a violent (N = 21) or a sexual (N = 12) offense. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
0
28
1
1
Order By: Relevance
“…Sondenaa and colleagues 55 screened all forensic examination reports (n = 3382) filed in the Norwegian Board of Forensic Medicine archives between 2001 and 2011 and found a diagnosis of ASD (based on ICD-10 criteria) 32 in 1% of the sample. Considering that a portion of the forensically examined individuals had not committed violent or sexual offenses, the ASD prevalence among violent/sexual offenders was therefore somewhere above 1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sondenaa and colleagues 55 screened all forensic examination reports (n = 3382) filed in the Norwegian Board of Forensic Medicine archives between 2001 and 2011 and found a diagnosis of ASD (based on ICD-10 criteria) 32 in 1% of the sample. Considering that a portion of the forensically examined individuals had not committed violent or sexual offenses, the ASD prevalence among violent/sexual offenders was therefore somewhere above 1%.…”
Section: Resultsmentioning
confidence: 99%
“…First, methodological differences among the prevalence studies cited—including differences in how “violence” was defined and measured, “type” of ASD examined (e.g., autism, AS), subject source, inclusion of non-ASD comparison groups, sample sizes, and method for diagnosing ASD—limit the ability to draw firm conclusions about violence risk factors in ASD or violence risk relative to the general population. Regarding the ASD diagnostic method, four of the prevalence studies 39 , 40 , 44 , 55 did not clearly incorporate robustly gathered developmental information into their assessments (via parent/relative interview regarding early development, review of childhood school/clinical records, or use of the Autism Diagnostic Interview–Revised 60 ), which is a significant limitation of those studies. Second, other potential generative risk factors for ASD-related violence (e.g., a history of psychological trauma) 106 were not emphasized, as the aim was to identify proposed risk factors based on multiple published reports.…”
Section: Limitationsmentioning
confidence: 99%
“…das Entblößen der eigenen Genitalien an öffentlichen Plätzen), häufiger kognitive und intellektuelle Beeinträchtigungen aufweisen sowie seltener eine ausreichende sexuelle Aufklärung und Erziehung erhalten haben. Darüber hinaus stellen sexuelle Übergriffe, begangen von Menschen mit einer Autismus-Spektrum-Störung, eher impulsive Handlungen dar (Søndenaa et al 2014).…”
Section: Bedeutung Der Autismus-spektrum-störungen Für Die Forensischunclassified
“…Lastly, a recent systematic review investigated the literature which explored sexual offending in individuals with ASD (Allely & Creaby-Attwood, 2016). The review highlighted that there were only a few case reports (N = 7) on sexual offending in individuals with ASD ( (Brendel, Bodkin, Hauptman, & Ornstein, 2002;Milton, Duggan, Latham, & Tantam, 2002;Murrie, Warren, Kistiansson, & Dietz, 2002;Ray, Marks, & Bray-Garretson, 2004;Haskins & Silva, 2006;Griffin-Shelley, 2010;Chan & Saluja, 2011) and only a small number of prevalence studies (N = 7) were identified (Mouridsen, Rich, Isager, & Nedergaard, 2008;Långström, Grann, Ruchkin, Sjöstedt, & Fazel, 2008;'t Hart-Kerkhoffs, Jansen, Doreleijers, Vermeiren, Minderaa, & Hartman, 2009;Kumagami & Matsuura, 2009;Bleil Walters et al, 2013;Søndenaa, Helverschou, Steindal, Rasmussen, Nilson, & Nøttestad, 2014). Some of the case studies identified in the review by Allely and Creaby-Attwood (2016) clearly highlight the need to consider these innate vulnerabilities which may increase the risk of an individual with ASD being charged with a sexual offence.…”
Section: Risk Factors For Inappropriate Sexual Behaviour or Sexual Ofmentioning
confidence: 99%